Arts meet antrhopology: possible reflections and dialogues - Freitag, Vanessa (Universidad Pedagógica y Tecnológica de Colombia, 2012)
The discussion in social sciences about arts and anthropology is not a new topic, although its influence on the contemporary researches is still a not so recurring fact. Exemplifying the importance of continuing with this problematic matter, —always thinking that both disciplines could methodologically and theoretically support and enrich each other— this article aims at presenting some possible relationships between arts and anthropology, focusing, on one hand, on the contributions accomplished by the contemporary visual anthropology through the work done by the Indigenous Photo Archive in Mexico, and on the other hand, to think, from the artistic filed, about Teresa Pereda’ work, whose visual poeticpresents appropriations that are usual features in the anthropological task: the look on others and their culture. According to the results found in this text, it is reinforced the premise that anthropology can learn from arts ways of thinking the visual thing, overall, when building the anthropological text, and that, anthropology in turn contributes in reconsidering the way to deal with the cultural differences, so recurrent in the poetic of some contemporaneous artists.